Implementasi E-Commerce Menggunakan Content Management System Untuk Mendukung Proses Penjualan Pada Family Gold Delivery - Naufal Noor Hibatulloh; Bima Cahya Putra; Lauw Li Hin; Agus Umar Hamdani (Asosiasi Pendidikan Tinggi Informatika dan Komputer Provinsi DKI Jakarta, 2023)
Family Gold Delivery is an online business that sells various brands of precious metals and also sells frame designs for precious metals that can be customized with greeting words according to the customer's wishes. In running its business, Family Gold Delivery only utilizes Instagram, Whatsapp and Marketplace media to sell its products. However, due to the high percentage of additional costs and insurance charged by the marketplace, it affects product prices, which must adjust to these costs, making buyers not want to transact through the marketplace. In the absence of a system to support the sales process, buyers still have to contact the seller directly via chat. Based on the existing problems, the solution provided is to apply the e-commerce model to the Family Gold Delivery business which aims to facilitate business processes, especially product sales activities. By using the Business Model Canvas (BMC) method to develop new business ideas to develop business strategies quickly and Fishbone Diagrams to analyze problems. Then the Wordpress Content Management System (CMS) as a tool for building websites so that the website can be implemented immediately and can meet all business needs. Accompanied by the implementation of Search Engine Optimization (SEO) and marketing strategies to expand marketing so as to produce an e-commerce website prototype that can support the sales process on Family Gold Delivery from sales to product marketing. The conclusion from the implementation of this e-commerce model can overcome the main problems faced by Family Gold Delivery namely, buyers will not be charged additional fees if transacting through e-commerce websites, and the sales process no longer needs to be done via chat.